Spain : Financial Sector Assessment Program-Technical Note-Systemic Risk Oversight Framework and Macroprudential Policy. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Spain in the areas of systemic risk oversight framework and macroprudential policy. Macroprudential oversight for banking is a shared responsibility between Banco de Espana (BdE) and the European Central Bank. The macroprudential policy stance appears broadly appropriate. BdE has put in place a framework for calibrating capital buffers. The countercyclical capital buffer is currently at zero given that a new financial cycle upturn has not started and a still-negative credit gap and weakly recovering housing prices. The existing macroprudential toolkit would benefit from expansion, particularly to include more effective tools to deal with risks associated with real estate exposures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet